Evidence for broad cross-reactivity of the SARS-CoV-2 NSP12-directed CD4+ T-cell response with pre-primed responses directed against common cold coronaviruses - Westphal, Tim; Mader, Maria; Karsten, Hendrik; Cords, Leon; Knapp, Maximilian; Schulte, Sophia; Hermanussen, Lennart; Peine, Sven; Ditt, Vanessa; Grifoni, Alba; Addo, Marylyn Martina; Huber, Samuel; et al. (Frontiers in Immunology, 2023)
Introduction The nonstructural protein 12 (NSP12) of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) has a high sequence identity with common cold coronaviruses (CCC). Methods Here, we comprehensively assessed the breadth and specificity of the NSP12-specific T-cell response after in vitro T-cell expansion with 185 overlapping 15-mer peptides covering the entire SARS-CoV-2 NSP12 at single-peptide resolution in a cohort of 27 coronavirus disease 2019 (COVID-19) patients. Samples of nine uninfected seronegative individuals, as well as five pre-pandemic controls, were also examined to assess potential cross-reactivity with CCCs. Results Surprisingly, there was a comparable breadth of individual NSP12 peptide-specific CD4+ T-cell responses between COVID-19 patients (mean: 12.82 responses; range: 0–25) and seronegative controls including pre-pandemic samples (mean: 12.71 responses; range: 0–21). However, the NSP12-specific T-cell responses detected in acute COVID-19 patients were on average of a higher magnitude. The most frequently detected CD4+ T-cell peptide specificities in COVID-19 patients were aa236–250 (37%) and aa246–260 (44%), whereas the peptide specificities aa686–700 (50%) and aa741–755 (36%), were the most frequently detected in seronegative controls. In CCC-specific peptide-expanded T-cell cultures of seronegative individuals, the corresponding SARS-CoV-2 NSP12 peptide specificities also elicited responses in vitro. However, the NSP12 peptide-specific CD4+ T-cell response repertoire only partially overlapped in patients analyzed longitudinally before and after a SARS-CoV-2 infection. Discussion The results of the current study indicate the presence of pre-primed, cross-reactive CCC-specific T-cell responses targeting conserved regions of SARS-CoV-2, but they also underline the complexity of the analysis and the limited understanding of the role of the SARS-CoV-2 specific T-cell response and cross-reactivity with the CCCs.